Exploring Article Process Charge of Open Access Journals from the Perspectives of Publication Characteristics and Citation Impact Indicators: A Case Study in the Medical Field - Chia-Yu Lin; Wen-Yau Cathy Lin (Jiàoyù zīliào yǔ túshūguǎn xué, 2022)
The complex APC operation mechanism of open access (OA) journal is generating discussion in the academic community. To understand the prices of APC, this study explored whether APC pricing in medicine is related to journal-related characteristics and journal influence-related indicators. In all,47 medicine-related fields in JCR-SCIE 2017 were collected, among which 3,420 journals had published OA articles and 2,037 OA journals were analyzed, which removal of duplicate titles and picking out fixed APC prices. Results showed that APCs and journal age were not significantly correlated; journals established earlier may have charged lower APCs than those established later. Overall, the majority of OA journals charged approximately US$3,000.APCs and publication frequency were positively correlated, APCs increased with publication frequency. APCs and the number of articles published were negatively correlated, perhaps because hybrid OA journals published fewer articles but charged higher APCs. Regarding journal influence, IF and II values were significantly correlated with APCs. With respect to rankings, for journals ranked in Q1 and Q4, correlations between ranking and APC were significant. This study suggests that future may use questionnaires or conduct in-depth interviews to gain insight into why authors submitted articles to OA journals, their willingness to submit the articles and how prices they were willing to pay in APCs.